Preparation method of environment-friendly water-based rubber protective film
Through the composite of styrene butadiene rubber and the use of nanomaterials, combined with pre-drying and high-temperature curing processes, the stability, drying speed and water resistance of the traditional rubber protective film are solved, and environmentally friendly and efficient preparation of water-based rubber protective film is achieved.
Patent Information
- Application Number
- CN202510941326.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-09
- Publication Date
- 2025-08-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional rubber protective films have problems such as poor emulsion stability, slow drying speed, insufficient water resistance, and difficulty in taking into account flexibility and adhesion. The solvent-based system pollutes the environment and endangers health.
Styrene butadiene rubber and nitrile rubber are mixed at a mass ratio of 3:1, nanosilica and silane coupling agent are added, and components such as sodium alginate, tributyl citrate, nano zinc oxide, chitosan and nanomontmorillonite are combined to form a stable aqueous rubber protective film through pre-drying and high-temperature curing process.
It improves the stability of the emulsion, improves the drying speed, enhances the mechanical strength and water resistance of the film layer, imparts antibacterial and antioxidant functions, and achieves environmentally friendly and efficient protection effects.
Smart Images

Figure CN120518897A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber chemical modification, in particular to a method for preparing an environmentally friendly water-based rubber protective film. Background Art
[0002] Traditional rubber protective films are mostly solvent-based systems, containing large amounts of volatile organic solvents. These release large amounts of volatile organic compounds during production and use, severely polluting the environment and endangering human health. Furthermore, solvent-based protective films pose safety risks such as flammability and explosion hazards. Furthermore, they lack flexibility after curing and are prone to cracking when bent or stretched, compromising their protective effectiveness.
[0003] Therefore, in recent years, water-based rubber protective film has gradually become a research hotspot, but it still faces the following technical difficulties: 1. Poor emulsion stability: Rubber particles in the water-based system are prone to coagulation or sedimentation, resulting in insufficient storage stability; 2. Slow drying speed: Water has a high latent heat of evaporation, so high temperature or long drying time is required, resulting in high energy consumption and low efficiency; 3. Insufficient water resistance: After the film is formed, it is easy to swell or fall off when exposed to water, which limits its application in humid environments; 4. It is difficult to balance adhesion and flexibility: Improving adhesion often causes the film layer to become harder and more brittle, while reducing adhesion will reduce the protective performance.
[0004] In summary, it is of great practical significance to develop a method for preparing an environmentally friendly, efficient and comprehensively excellent water-based rubber protective film. Summary of the Invention
[0005] The object of the present invention is to provide a method for preparing an environmentally friendly water-based rubber protective film to solve the problems raised in the above background technology.
[0006] In view of the above problems, the technical solution proposed by the present invention is: A method for preparing an environmentally friendly water-based rubber protective film comprises the following steps: S1. Styrene-butadiene rubber and nitrile rubber are mixed in a mass ratio of 3:1 to prepare an emulsion with a solid content of 40-50%, nano-silica and a silane coupling agent are added, and the mixture is reacted at 50-60°C for 2-3 hours to obtain a silane-modified rubber emulsion. By compounding styrene-butadiene rubber and nitrile rubber, the advantages of both can be combined to improve the flexibility, wear resistance and oil resistance of the protective film; the addition of nano-silica can enhance the mechanical strength and wear resistance of the film layer, and the silane coupling agent can improve the compatibility of nanoparticles with the rubber matrix, thereby improving the emulsion stability and the overall performance of the film layer; S2. Sodium alginate is prepared into a 2-3% aqueous solution, tributyl citrate and nano zinc oxide are added, and ultrasonic dispersion is performed for 30 minutes to obtain a composite crosslinking agent solution. Sodium alginate, tributyl citrate and nano zinc oxide form a composite crosslinking agent, which can undergo a cross-linking reaction with rubber molecules during the film formation process to improve the water resistance, mechanical strength and thermal stability of the film layer; ultrasonic dispersion can evenly disperse the nano zinc oxide, giving full play to its antibacterial and reinforcing effects; S3. Dissolve chitosan in acetic acid solution, add propyl gallate and nano-montmorillonite, and stir to mix evenly to obtain a functional additive solution. Chitosan has the characteristics of antibacterial and good film-forming properties, and can give the protective film an antibacterial function; propyl gallate, as an antioxidant, can improve the antioxidant properties of the protective film and delay aging; nano-montmorillonite can enhance the barrier properties, mechanical strength and water resistance of the film layer; S4, adding the composite cross-linking agent solution and the functional additive solution to the modified rubber latex, followed by stirring for 1-2 hours, then adding a defoaming agent and a preservative, and adjusting the pH value to 8-9 to obtain a mixed emulsion, so that the components are fully mixed to form a stable mixed emulsion; the defoaming agent can eliminate bubbles in the emulsion and avoid defects such as pores in the film layer; the preservative can prevent the emulsion from breeding microorganisms during storage and extend the storage period; adjusting the pH value to a weak alkaline value can improve the stability of the emulsion; S5. Apply the mixed emulsion to the surface of the substrate, pre-dry at 60-80℃ for 5-10 minutes, and then cure at 120-150℃ for 10-15 minutes to form an environmentally friendly water-based rubber protective film. Pre-drying can remove most of the water in the mixed emulsion, reduce energy consumption and time during curing, and avoid defects in the film layer due to rapid evaporation of water; high-temperature curing can promote the full cross-linking reaction, so that the film layer has good mechanical properties, water resistance and weather resistance.
[0007] As a preferred technical solution of the present invention, the particle size of the nano-silica is 20-50 nm, and the addition amount is 2-5% of the total mass of styrene-butadiene rubber and nitrile rubber. The appropriate particle size and addition amount can make the nano-silica uniformly dispersed in the rubber emulsion, give full play to its reinforcing and toughening effects, improve the mechanical strength and wear resistance of the film layer, and at the same time avoid the increase in emulsion viscosity and decrease in stability due to excessive addition.
[0008] As a preferred technical solution of the present invention, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the addition amount is 1-3% of the total mass of styrene-butadiene rubber and nitrile rubber. The silane coupling agent can effectively improve the compatibility of nano-silica with the rubber matrix, improve the stability of the emulsion and the comprehensive performance of the film layer. The appropriate addition amount can reduce costs while ensuring the modification effect.
[0009] As a preferred technical solution of the present invention, the styrene content of the styrene-butadiene rubber is 23-25%, and the Mooney viscosity is 40-50; the acrylonitrile content of the nitrile rubber is 33-35%, and the Mooney viscosity is 50-60. The specific styrene content and Mooney viscosity can make the styrene-butadiene rubber have good elasticity and processing properties; the appropriate acrylonitrile content and Mooney viscosity can make the nitrile rubber have excellent oil resistance and solvent resistance. The combination of the two can make the protective film have good comprehensive properties.
[0010] As a preferred technical solution of the present invention, the particle size of the nano zinc oxide is 50-100 nm, and the addition amount is 5-8% of the mass of sodium alginate. The appropriate particle size and addition amount can make the nano zinc oxide uniformly dispersed in the composite crosslinker solution, fully exert its antibacterial, crosslinking and reinforcing effects, and improve the antibacterial properties, mechanical strength and water resistance of the film layer.
[0011] As a preferred technical solution of the present invention, the chitosan has a deacetylation degree of ≥90%, and the addition amount is 2% of the mass of the functional additive solution. Chitosan with a high deacetylation degree has better film-forming, antibacterial and cationic properties. The appropriate addition amount can make the functional additive solution have good antibacterial properties and stability without affecting the performance of the mixed emulsion.
[0012] As a preferred technical solution of the present invention, the nano-montmorillonite is an organically modified type, has a cation exchange capacity of 90-120 mmol / 100 g, and is added in an amount of 3-5% of the mass of chitosan. The organically modified nano-montmorillonite has good lipophilicity and can be better compatible with the rubber matrix. The appropriate cation exchange capacity and addition amount can enable the nano-montmorillonite to form a uniform intercalation structure in the film layer, thereby improving the barrier properties, mechanical strength and water resistance of the film layer.
[0013] As a preferred technical solution of the present invention, the addition amount of the composite crosslinker solution is 5-10% of the mass of the modified rubber latex, and the addition amount of the functional additive solution is 3-8% of the mass of the modified rubber latex. The appropriate addition amount can enable the composite crosslinker and functional additive to fully react with the modified rubber latex, thereby improving the crosslinking density, antibacterial properties, antioxidant properties and barrier properties of the film layer, while ensuring the stability and processing performance of the mixed emulsion.
[0014] As a preferred technical solution of the present invention, the defoaming agent is a silicone defoaming agent, and the added amount is 0.5-1% of the mass of the modified rubber emulsion; the preservative is kason, and the added amount is 0.3-0.5% of the mass of the modified rubber emulsion. The silicone defoaming agent can effectively eliminate bubbles in the mixed emulsion and avoid defects such as pores in the film layer; the kason preservative can inhibit the growth and reproduction of microorganisms, extend the storage period of the mixed emulsion, and ensure the stability of the emulsion.
[0015] As a preferred technical solution of the present invention, the solid content of the mixed emulsion is 35-45%, and the coating thickness is 50-100 μm. The appropriate solid content can make the mixed emulsion have good construction performance and be easy to coat; the appropriate coating thickness can make the protective film have good mechanical properties, protective properties and appearance quality.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: the preparation method of the environmentally friendly water-based rubber protective film, through compounding styrene-butadiene rubber and nitrile rubber in a mass ratio of 3:1, with the synergistic effect of components such as nano-silica, silane coupling agent, sodium alginate, tributyl citrate, nano-zinc oxide, chitosan, propyl gallate and organically modified nano-montmorillonite, combined with the process optimization of pre-drying and high-temperature curing, can solve the problems of poor emulsion stability, slow drying speed, insufficient water resistance and difficulty in balancing flexibility and adhesion in the existing water-based protective film, and at the same time give the protective film antibacterial, antioxidant and other functions, improve its mechanical strength, weather resistance and environmental protection, and achieve efficient protection for various substrates. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The present invention is a schematic diagram of a process for preparing an environmentally friendly water-based rubber protective film disclosed in an embodiment of the present invention. DETAILED DESCRIPTION
[0018] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0019] Example 1 See also Figure 1 The present invention provides a technical solution: a method for preparing an environmentally friendly water-based rubber protective film, comprising the following steps: S1. Styrene-butadiene rubber and nitrile rubber are mixed in a mass ratio of 3:1 to prepare an emulsion with a solid content of 40-50%, nano-silica and a silane coupling agent are added, and the mixture is reacted at 50-60°C for 2-3 hours to obtain a silane-modified rubber emulsion. Styrene-butadiene rubber imparts good flexibility and elasticity to the material, while nitrile rubber provides oil resistance and solvent resistance. The two are compounded in a ratio of 3:1 to form a rubber matrix with complementary properties; nano-silica is used as a reinforcing filler and is uniformly dispersed in the rubber emulsion to play a physical reinforcing role; the silicon-oxygen bond in the silane coupling agent molecule reacts with the hydroxyl group on the surface of the nano-silica, and the organic group at the other end physically entangles or chemically reacts with the rubber molecular chain to form an interfacial bonding force, thereby improving compatibility and emulsion stability; S2. Sodium alginate is prepared into a 2-3% aqueous solution, tributyl citrate and nano zinc oxide are added, and ultrasonic dispersion is performed for 30 minutes to obtain a composite crosslinker solution. The carboxyl groups in the sodium alginate molecules can form hydrogen bonds or ionic crosslinking with the active groups in the rubber molecules; tributyl citrate acts as a plasticizer to improve the flexibility of the film layer and participate in the crosslinking reaction to increase the crosslinking density of the film layer; nano zinc oxide not only has antibacterial properties, but also can form ionic bonds with sodium alginate to enhance the crosslinking effect; ultrasonic dispersion breaks the agglomeration of nano zinc oxide through high-frequency vibration, so that it is evenly dispersed in the solution, ensuring that the crosslinking reaction proceeds evenly; S3. Dissolve chitosan in acetic acid solution, add propyl gallate and nano-montmorillonite, and stir to mix evenly to obtain a functional additive solution. Chitosan dissolves in the acetic acid solution to form a positively charged polymer solution, which can generate electrostatic interaction with negatively charged rubber particles to improve the stability of the emulsion. At the same time, the amino and hydroxyl groups on its molecular chain can form hydrogen bonds with rubber molecules to enhance the adhesion of the film layer; the phenolic hydroxyl group of propyl gallate can capture free radicals and inhibit the oxidation reaction of the film layer; the nano-montmorillonite has a layered structure and is evenly dispersed in the film layer to form a barrier to hinder the penetration of water molecules and oxygen. At the same time, its layers can be intercalated with rubber molecules to improve the strength and toughness of the film layer; S4, adding the composite crosslinking agent solution and the functional additive solution to the modified rubber latex, followed by stirring for 1-2 hours, then adding a defoaming agent and a preservative, and adjusting the pH value to 8-9 to obtain a mixed emulsion, wherein the composite crosslinking agent solution and the functional additive solution are uniformly dispersed in the modified rubber latex by stirring, and the components are fully in contact with each other, laying a foundation for subsequent crosslinking reaction and functional performance; the defoaming agent reduces the surface tension of the emulsion, causing the bubbles to burst and be discharged; the preservative destroys the cell structure or metabolic process of microorganisms, inhibiting their growth and reproduction; adjusting the pH value to a weak alkaline value can neutralize the acidic substances in the emulsion, stabilize the charge on the surface of the rubber particles, reduce the agglomeration between the particles, and improve the storage stability of the emulsion; S5. Apply the mixed emulsion to the surface of the substrate, pre-dry at 60-80°C for 5-10 minutes, and then cure at 120-150°C for 10-15 minutes to form an environmentally friendly water-based rubber protective film. During the pre-drying stage, at 60-80°C, the water in the emulsion gradually evaporates, the rubber particles approach each other and begin to form a preliminary network structure; during the curing stage, at a high temperature of 120-150°C, the composite cross-linking agent and the rubber molecules undergo a sufficient cross-linking reaction to form a three-dimensional network structure. At the same time, the functional additives are further combined with the rubber matrix, so that the strength, water resistance, weather resistance and other properties of the film layer are significantly improved, and finally an environmentally friendly water-based rubber protective film with excellent performance is formed.
[0020] As an embodiment of the present invention, further, the particle size of nano-silica is 20-50nm, and the addition amount is 2-5% of the total mass of styrene-butadiene rubber and nitrile rubber. Nano-silica of 20-50nm has a large specific surface area and surface energy, can form a strong interfacial bonding force with the rubber molecules, and play an effective reinforcing role; the addition amount is controlled at 2-5%, which can ensure the reinforcing effect while avoiding the agglomeration of nanoparticles and maintaining the stability and processing performance of the emulsion.
[0021] As an embodiment of the present invention, further, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the added amount is 1-3% of the total mass of styrene-butadiene rubber and nitrile rubber. The trimethoxysilyl group in the γ-methacryloxypropyltrimethoxysilane molecule can undergo hydrolysis and condensation reaction with the hydroxyl group on the surface of the nano-silica to form a strong Si-O-Si bond, and the methacryloyloxy group at the other end can undergo free radical polymerization reaction or physical entanglement with the double bond in the rubber molecule, thereby forming a bridge between the nano-silica and the rubber matrix, enhancing the interfacial bonding force and improving the compatibility.
[0022] As an embodiment of the present invention, further, the styrene content of styrene-butadiene rubber is 23-25%, and the Mooney viscosity is 40-50; the acrylonitrile content of nitrile rubber is 33-35%, and the Mooney viscosity is 50-60. The styrene content of styrene-butadiene rubber affects its elasticity, wear resistance and processing properties. A styrene content of 23-25% can make styrene-butadiene rubber have both good elasticity and processing properties; the Mooney viscosity reflects the average molecular weight of the rubber and the flexibility of the molecular chain. A Mooney viscosity of 40-50 makes styrene-butadiene rubber have suitable fluidity and processing properties; the acrylonitrile content of nitrile rubber determines its oil resistance. An acrylonitrile content of 33-35% can make nitrile rubber have good oil resistance while maintaining a certain elasticity; a Mooney viscosity of 50-60 makes nitrile rubber have good processing properties. The two are compounded in proportion to form a rubber matrix with complementary properties in the protective film.
[0023] As an embodiment of the present invention, further, the particle size of nano zinc oxide is 50-100 nm, and the addition amount is 5-8% of the mass of sodium alginate. Nano zinc oxide of 50-100 nm has good antibacterial activity and dispersibility, can be evenly distributed in the film layer, and has a long-lasting antibacterial effect; the addition amount is 5-8% of the mass of sodium alginate, which can make nano zinc oxide and sodium alginate fully react to form a stable ionic cross-linking structure, enhance the cross-linking density and mechanical strength of the film layer, and at the same time improve the water resistance of the film layer.
[0024] As an embodiment of the present invention, further, the deacetylation degree of chitosan is ≥90%, and the addition amount is 2% of the mass of the functional additive solution. The chitosan molecules with a deacetylation degree ≥90% contain more amino groups, which makes them have stronger cationicity and reactivity, and can better interact with rubber particles, improve emulsion stability and film adhesion, and have better antibacterial properties; the addition amount is 2% of the mass of the functional additive solution, which can ensure the antibacterial effect while avoiding the increase in the viscosity of the functional additive solution due to excessive chitosan content, affecting its mixing with the modified rubber latex.
[0025] As an embodiment of the present invention, further, the nano-montmorillonite is an organically modified type, with a cation exchange capacity of 90-120 mmol / 100 g, and an addition amount of 3-5% of the mass of chitosan. The lipophilic groups on the surface of the organically modified nano-montmorillonite can physically entangle or chemically react with the rubber molecules, thereby improving its compatibility with the rubber matrix; the nano-montmorillonite with a cation exchange capacity of 90-120 mmol / 100 g has an appropriate number of interlayer cations, which can undergo ion exchange reaction with the amino groups in the chitosan molecules to form an intercalated structure, so that the layered structure of the nano-montmorillonite is evenly dispersed in the film layer, forming a barrier and enhancing the mechanical strength and water resistance of the film layer; the addition amount is 3-5% of the mass of chitosan, which can avoid the agglomeration of nano-montmorillonite while ensuring the barrier and reinforcement effects, thereby maintaining the flexibility of the film layer.
[0026] As an embodiment of the present invention, further, the addition amount of the composite crosslinker solution is 5-10% of the mass of the modified rubber latex, and the addition amount of the functional additive solution is 3-8% of the mass of the modified rubber latex. The addition amount of the composite crosslinker solution is 5-10% of the mass of the modified rubber latex, which can provide sufficient crosslinking points to enable the rubber molecules to form a moderate three-dimensional network structure, thereby improving the mechanical strength, water resistance and thermal stability of the film layer; the addition amount of the functional additive solution is 3-8% of the mass of the modified rubber latex, which can enable chitosan, propyl gallate and nano-montmorillonite to fully exert their antibacterial, antioxidant, barrier and reinforcing effects in the film layer, while avoiding affecting the stability of the mixed emulsion and the flexibility of the film layer due to excessive addition.
[0027] As an embodiment of the present invention, further, the defoaming agent is a silicone defoaming agent, and the added amount is 0.5-1% of the mass of the modified rubber latex; the preservative is kason, and the added amount is 0.3-0.5% of the mass of the modified rubber latex. The silicone defoaming agent has low surface tension and good spreading properties, and can spread rapidly on the surface of the bubble, reduce the surface tension of the bubble film, and cause the bubble to burst and discharge; the added amount is 0.5-1% of the mass of the modified rubber latex, which can ensure the defoaming effect while avoiding the influence of excessive defoaming agent on the stability of the emulsion; the active ingredient in the kason preservative can react with the sulfhydryl group in the microbial cells, destroy the cell structure and enzyme system of the microorganism, and inhibit its growth and reproduction; the added amount is 0.3-0.5% of the mass of the modified rubber latex, which can ensure the anti-corrosion effect while reducing the harm to the environment and human body.
[0028] As an embodiment of the present invention, further, the solid content of the mixed emulsion is 35-45%, and the coating thickness is 50-100 μm. The mixed emulsion with a solid content of 35-45% has suitable viscosity and fluidity, which is convenient for being evenly coated on the surface of the substrate by spraying, scraping, etc.; the coating thickness is 50-100 μm, which can make the protective film form a continuous film layer with a certain thickness on the surface of the substrate, ensuring that it has good mechanical strength, water resistance, weather resistance and protective performance, while avoiding the extension of drying time due to the film layer being too thick, the film layer becoming hard and brittle, or the insufficient protective performance due to the film layer being too thin.
[0029] Example 2 See also Figure 1 The present invention provides a technical solution: a method for preparing an environmentally friendly water-based rubber protective film, comprising the following steps: S1. Add 300g of styrene-butadiene rubber and 100g of nitrile rubber to 1200g of deionized water, stir and disperse them evenly; add 10g of nano-silica and 5g of γ-methacryloxypropyltrimethoxysilane, and react at 55°C for 2.5 hours to obtain a silane-modified rubber latex.
[0030] S2. Dissolve 5 g of sodium alginate in 250 g of deionized water, add 0.75 g of tributyl citrate and 0.4 g of nano zinc oxide, and disperse by ultrasonication for 30 minutes to obtain a composite crosslinking agent solution.
[0031] S3. Dissolve 5 g of chitosan in 250 g of 1% acetic acid solution, add 0.3 g of propyl gallate and 0.2 g of nano-montmorillonite, and stir to mix well to obtain a functional additive solution.
[0032] S4. Under stirring at 1200 rpm, add 100 g of the composite crosslinker solution and 60 g of the functional additive solution in sequence, and continue stirring for 1.5 hours; add 8 g of the defoamer and 4 g of the preservative, and adjust the pH to 8.5 with aqueous ammonia to obtain a mixed emulsion.
[0033] S5. Apply the emulsion to the surface of the aluminum plate, pre-dry at 60°C for 8 minutes, and cure at 130°C for 12 minutes to form an environmentally friendly water-based rubber protective film.
[0034] Example 3 See also Figure 1 The present invention provides a technical solution: a method for preparing an environmentally friendly water-based rubber protective film, comprising the following steps: S1. Add 450g of styrene-butadiene rubber and 150g of nitrile rubber to 1500g of deionized water, stir and disperse them evenly; add 15g of nano-silica and 7.5g of γ-methacryloxypropyltrimethoxysilane, and react at 50°C for 3 hours to obtain a silane-modified rubber latex.
[0035] S2. Dissolve 7.5 g of sodium alginate in 300 g of deionized water, add 1.1 g of tributyl citrate and 0.6 g of nano zinc oxide, and disperse by ultrasonication for 30 minutes to obtain a composite crosslinking agent solution.
[0036] S3. Dissolve 7.5 g of chitosan in 300 g of 1% acetic acid solution, add 0.5 g of propyl gallate and 0.3 g of organically modified nano-montmorillonite, and stir to mix well to obtain a functional additive solution.
[0037] S4. Under stirring conditions of 1000 rpm, 150 g of the composite crosslinking agent solution and 90 g of the functional additive solution were added in sequence, and stirring was continued for 2 hours; 12 g of the silicone defoamer and 6 g of the Kathon preservative were added, and the pH was adjusted to 8.8 with aqueous ammonia to obtain a mixed emulsion.
[0038] S5. Apply the emulsion to the surface of the stainless steel substrate, pre-dry at 70°C for 10 minutes, and cure at 120°C for 15 minutes to form an oil-resistant protective film.
[0039] Example 4 See also Figure 1 The present invention provides a technical solution: a method for preparing an environmentally friendly water-based rubber protective film, comprising the following steps: S1. Add 300g of styrene-butadiene rubber and 100g of nitrile rubber to 1200g of deionized water, stir and disperse them evenly; add 8g of nano-silica and 3g of γ-methacryloxypropyltrimethoxysilane, and react at 60°C for 2 hours to obtain a silane-modified rubber latex.
[0040] S2. Dissolve 10 g of sodium alginate in 400 g of deionized water, add 1.5 g of tributyl citrate and 0.8 g of nano zinc oxide, and disperse by ultrasonication for 30 minutes to obtain a composite crosslinking agent solution.
[0041] S3. Dissolve 10 g of chitosan in 400 g of 1% acetic acid solution, add 0.8 g of propyl gallate and 0.5 g of organically modified nano-montmorillonite, and stir to mix well to obtain a functional additive solution.
[0042] S4. Under stirring conditions of 1500 rpm, 120 g of the composite crosslinking agent solution and 70 g of the functional additive solution were added in sequence, and stirring was continued for 1 hour; 10 g of the defoaming agent and 5 g of the preservative were added, and the pH was adjusted to 9.0 to obtain a mixed emulsion.
[0043] S5. Apply the emulsion to the surface of the plastic substrate, pre-dry at 65°C for 7 minutes, and cure at 140°C for 10 minutes to form a protective film with high antibacterial properties.
[0044] Example 5 See also Figure 1 The present invention provides a technical solution: a method for preparing an environmentally friendly water-based rubber protective film, comprising the following steps: S1. Add 240 g of styrene-butadiene rubber and 80 g of nitrile rubber to 1000 g of deionized water to prepare an emulsion with a solid content of 40%; add 6 g of nano-silica and 2.4 g of silane coupling agent, and react at 55° C. for 2.5 hours.
[0045] S2. Dissolve 4 g of sodium alginate in 200 g of deionized water, add 0.6 g of tributyl citrate and 0.32 g of nano zinc oxide, and disperse by ultrasonication for 30 minutes.
[0046] S3. Dissolve 4 g of chitosan in 200 g of 1% acetic acid solution, add 0.2 g of propyl gallate and 0.12 g of nano-montmorillonite, and stir to mix well.
[0047] S4. Add 80 g of the composite crosslinking agent solution and 48 g of the functional additive solution while stirring at 1200 rpm, and stir for 1.5 hours; add 6 g of the defoaming agent and 3 g of the preservative, and adjust the pH to 8.5.
[0048] S5. The emulsion is applied to the surface of the glass substrate, pre-dried at 80° C. for 5 minutes, and cured at 150° C. for 12 minutes to form an ultra-thin flexible protective film with a thickness of 50 μm.
[0049] Table 1: Performance comparison of Examples 2 to 5 with commercially available products Performance indicators Example 2 Example 3 Example 4 Example 5 Commercially available products Tensile strength (MPa) 8.5 9.2 8.8 7.5 5.2 Elongation at break (%) 420 380 400 450 310 Water resistance (24h) No change No change No change No change Slight swelling Adhesion (grade) 0 0 0 0 1 Volatile organic compound content (g / L) <10 <10 <10 <10 >150 Antibacterial rate (%) 98.5 95 99 90 none As can be seen from Table 1, the tensile strength of the protective film prepared by this technical solution is 7.5-9.2MPa, while that of the commercially available product is 5.2MPa; the elongation at break is 380%-450%, while that of the commercially available product is 310%. This solution is superior in both strength and flexibility, and can better adapt to the protection needs of different substrates; the product of this solution has no change after a 24-hour water resistance test, while the commercially available product will swell slightly, and the product of this solution is more suitable for use in humid environments; the adhesion of the product of this solution reaches level 0, while that of the commercially available product is level 1. It can be seen that the product of this solution has a better applicability in humid environments. The product is more firmly bonded to the substrate and is not easy to fall off; this technical solution adopts a water-based system with a VOC content of less than 10g / L, which meets environmental protection standards; while most commercially available products are solvent-based systems with a VOC content of more than 150g / L, which will release a large amount of volatile organic compounds during production and use, polluting the environment and endangering human health; this technical solution can give the protective film antibacterial, oil-resistant and other functions by adjusting the formula and process. For example, the highly antibacterial product of Example 4 has an antibacterial rate of 99%, while commercially available products usually do not have these functions and have relatively single application scenarios.
Claims
1. A method for preparing an environmentally friendly water-based rubber protective film, characterized in that: The following steps are involved: S1. Styrene-butadiene rubber and nitrile-butadiene rubber are mixed in a mass ratio of 3:1 to prepare an emulsion with a solid content of 40-50%, nano-silica and a silane coupling agent are added, and the mixture is reacted at 50-60° C. for 2-3 hours to obtain a silane-modified rubber emulsion; S2. Prepare a 2-3% aqueous solution of sodium alginate, add tributyl citrate and nano zinc oxide, and ultrasonically disperse for 30 minutes to obtain a composite crosslinking agent solution; S3, dissolving chitosan in acetic acid solution, adding propyl gallate and nano-montmorillonite, stirring and mixing to obtain a functional additive solution; S4, adding the composite crosslinking agent solution and the functional additive solution to the modified rubber latex, followed by stirring for 1-2 hours, adding a defoaming agent and a preservative, and adjusting the pH value to 8-9 to obtain a mixed emulsion; S5. Apply the mixed emulsion to the surface of the substrate, pre-dry at 60-80°C for 5-10 minutes, and then cure at 120-150°C for 10-15 minutes to form an environmentally friendly water-based rubber protective film.
2. The method for preparing an environmentally friendly water-based rubber protective film according to claim 1, characterized in that: The particle size of the nano-silicon dioxide is 20-50 nm, and the added amount is 2-5% of the total mass of styrene-butadiene rubber and nitrile-butadiene rubber.
3. The method for preparing an environmentally friendly water-based rubber protective film according to claim 1, characterized in that: The silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the added amount is 1-3% of the total mass of styrene-butadiene rubber and nitrile rubber.
4. The method for preparing an environmentally friendly water-based rubber protective film according to claim 1, characterized in that: The styrene content of the styrene-butadiene rubber is 23-25%, and the Mooney viscosity is 40-50; the acrylonitrile content of the nitrile-butadiene rubber is 33-35%, and the Mooney viscosity is 50-60.
5. The method for preparing an environmentally friendly water-based rubber protective film according to claim 1, characterized in that: The particle size of the nano zinc oxide is 50-100 nm, and the added amount is 5-8% of the mass of the sodium alginate.
6. The method for preparing an environmentally friendly water-based rubber protective film according to claim 1, characterized in that: The deacetylation degree of the chitosan is ≥90%, and the added amount is 2% of the mass of the functional additive solution.
7. The method for preparing an environmentally friendly water-based rubber protective film according to claim 1, characterized in that: The nano-montmorillonite is of organic modified type, has a cation exchange capacity of 90-120 mmol / 100 g, and is added in an amount of 3-5% of the mass of chitosan.
8. The method for preparing an environmentally friendly water-based rubber protective film according to claim 1, characterized in that: The addition amount of the composite cross-linking agent solution is 5-10% of the mass of the modified rubber latex, and the addition amount of the functional additive solution is 3-8% of the mass of the modified rubber latex.
9. The method for preparing an environmentally friendly water-based rubber protective film according to claim 1, characterized in that: The defoaming agent is an organosilicon defoaming agent, and the addition amount is 0.5-1% of the mass of the modified rubber latex; the preservative is kason, and the addition amount is 0.3-0.5% of the mass of the modified rubber latex.
10. The method for preparing an environmentally friendly water-based rubber protective film according to claim 1, characterized in that: The solid content of the mixed emulsion is 35-45%, and the coating thickness is 50-100 μm.
Citation Information
Cited By
High-barrier polyethylene / montmorillonite composite material and preparation method thereof
CN122234492A